Carfilzomib, bendamustine, and dexamethasone in patients with advanced multiple myeloma: The EMN09 phase 1/2 study of the European Myeloma Network - Gay, Francesca; Guenther, Andreas; Offidani, Massimo; Engelhardt, Monika; Salvini, Marco; Montefusco, Vittorio; Patriarca, Francesca; Aquino, Sara; Poenisch, Wolfram; Spada, Stefano; Schub, Natalie; Gentili, Silvia; et al. (Cancer, 2021)
Background: Combined therapy with carfilzomib, bendamustine, and dexamethasone was evaluated in this multicenter phase 1/2 trial conducted within the European Myeloma Network (EMN09 trial). Methods: Sixty-three patients with relapsed/refractory multiple myeloma who had received ≥2 lines of prior therapy were included. The phase 1 portion of the study determined the maximum tolerated dose of carfilzomib with bendamustine set at 70 mg/m2 on days 1 and 8. After 8 cycles, responding patients received maintenance therapy with carfilzomib and dexamethasone until progression. Results: On the basis of the phase 1 results, the recommended phase 2 dose for carfilzomib was 27 mg/m2 twice weekly in weeks 1, 2, and 3. Fifty-two percent of patients achieved a partial response or better, and 32% reached a very good partial response or better. The clinical benefit rate was 93%. After a median follow-up of 21.9 months, the median progression-free survival was 11.6 months, and the median overall survival was 30.4 months. The reported grade ≥3 hematologic adverse events (AEs) were lymphopenia (29%), neutropenia (25%), and thrombocytopenia (22%). The main nonhematologic grade ≥3 AEs were pneumonia, thromboembolic events (10%), cardiac AEs (8%), and hypertension (2%). Conclusions: In heavily pretreated patients who have relapsed/refractory multiple myeloma, combined carfilzomib, bendamustine, and dexamethasone is an effective treatment option administered in the outpatient setting. Infection prophylaxis and attention to patients with cardiovascular predisposition are required.
CRIS-Team Scopus Importer:2023-03-23
Keywords: bendamustine; carfilzomib; multiple myeloma; phase 1/2 study